Adoption of evidence-based medicine: A comparative study of hospital and community pharmacists in Saudi Arabia - Fahad Alzahrani; Nawaf Almutairi; Abdullah Aloufi; Abdulmalik Kattan; Abdulaziz Hakeem; Mohammed Alharbi; Naif Alarawi; Haifa A. Fadil; Ehsan Habeeb (PLoS ONE, 2025)
Objectives Evidence-based medicine (EBM) combines clinical expertise, patient values, and the best available evidence to guide healthcare decision-making. Despite its importance in pharmacy practice, EBM adoption in Saudi Arabian pharmacies remains under-researched. This study aimed to assess the knowledge, attitudes, and practices regarding EBM among hospital and community pharmacists in the Madinah Region, Saudi Arabia. Methods A cross-sectional study was conducted with 206 pharmacists from September to November 2023. Data were collected through a validated online self-administered questionnaire to evaluate pharmacists’ knowledge, attitude, and practice (KAP), as well as their understanding of EBM technical terms. Ethical approval The study was approved by the Scientific Ethics Committee of the College of Pharmacy at Taibah University, Madinah region, Saudi Arabia (reference number COPTU-REC-77–20230827). All participants received a consent form before participating. Results Pharmacists demonstrated moderate knowledge (76.5%), neutral attitudes (76%), and fair practices (68%) toward EBM, with hospital pharmacists scoring higher than community pharmacists. Moreover, 83.3% believed that EBM could enhance patient health outcomes, 80.0% were willing to learn, and 35.9% believed that EBM focuses solely on research without considering clinical experience. Time constraints (34.0%) were a major barrier, and 46.1% of the participants lacked appropriate training. EBM education was correlated with higher knowledge and attitude scores; however, it had no significant impact on practice scores. Significant barriers identified were the difficulty in conveying technical terms (16%) and limited access to adequate training opportunities. Conclusion Despite positive attitudes toward EBM, many pharmacists perceive it as a potential threat to good clinical practice. This perception underscores the need for targeted educational initiatives that promote EBM benefits, address misconceptions, and provide practical support for its integration in both hospital and community pharmacy settings.